Determination of Corneal Biomechanical Behavior in-vivo for Healthy Eyes Using CorVis ST Tonometry: Stress-Strain Index - Eliasy, Ashkan; Chen, Kai-Jung; Vinciguerra, Riccardo; Lopes, Bernardo T.; Abass, Ahmed; Vinciguerra, Paolo; Ambrósio Jr., Renato; Roberts, Cynthia J.; Elsheikh, Ahmed (Frontiers in Bioengineering and Biotechnology, 2019)
Purpose: This study aims to introduce and clinically validate a new algorithm that can determine the biomechanical properties of the human cornea in vivo. Methods: A parametric study was conducted involving representative finite element models of human ocular globes with wide ranges of geometries and material biomechanical behaviour. The models were subjected to different levels of intraocular pressure (IOP) and the action of external air puff produced by a non-contact tonometer. Predictions of dynamic corneal response under air pressure were analysed to develop an algorithm that can predict the cornea’s material behaviour. The algorithm was assessed using clinical data obtained from 480 healthy participants where its predictions of material behaviour were tested against variations in central corneal thickness (CCT), IOP and age, and compared against those obtained in earlier studies on ex-vivo human ocular tissue. Results: The algorithm produced a material stiffness parameter (Stress-Strain Index or SSI) that showed no significant correlation with both CCT (p> 0.05) and IOP (p> 0.05), but was significantly correlated with age (p< 0.01). The stiffness estimates and their variation with age were also significantly correlated (p< 0.01) with stiffness estimates obtained earlier in studies on ex-vivo human tissue. Conclusions: The study introduced and validated a new method for estimating the in vivo biomechanical behavior of healthy corneal tissue. The method can aid optimization of procedures that interfere mechanically with the cornea such as refractive surgeries and introduction of corneal implants.